Strigolactones suppress adventitious rooting in Arabidopsis and pea. - Rasmussen, A; Mason, MG; De Cuyper, C; Brewer, P; Herold, S; Agusti, J; Geelen, D; Greb, T; Goormachtig, S; Beeckman, T; Beveridge, C (2012)
Adventitious root formation is essential for the propagation of many commercially important plant species and involves the formation of roots from nonroot tissues such as stems or leaves. Here, we demonstrate that the plant hormone strigolactone suppresses adventitious root formation in Arabidopsis (Arabidopsis thaliana) and pea (Pisum sativum). Strigolactone-deficient and response mutants of both species have enhanced adventitious rooting. CYCLIN B1 expression, an early marker for the initiation of adventitious root primordia in Arabidopsis, is enhanced in more axillary growth2 (max2), a strigolactone response mutant, suggesting that strigolactones restrain the number of adventitious roots by inhibiting the very first formative divisions of the founder cells. Strigolactones and cytokinins appear to act independently to suppress adventitious rooting, as cytokinin mutants are strigolactone responsive and strigolactone mutants are cytokinin responsive. In contrast, the interaction between the strigolactone and auxin signaling pathways in regulating adventitious rooting appears to be more complex. Strigolactone can at least partially revert the stimulatory effect of auxin on adventitious rooting, and auxin can further increase the number of adventitious roots in max mutants. We present a model depicting the interaction of strigolactones, cytokinins, and auxin in regulating adventitious root formation.